Writing Care: Narrative Strategies and Corporeal Realities in Carmen Maria Machado's In the Dream House - Angel Maria Varghese; Arka Chattopadhyay (European Journal of Life Writing)
In this paper, we analyze Carmen Maria Machado’s memoir In the Dream House (2019), focusing on care and corporeality, attending to the intricacies of its narrative form. We argue that Machado not only presents abuse, care, and corporeality as themes but also embeds them as integral elements shaping the form of the narrative. By doing so, she expands the formal possibilities of life writing, inviting readers to reconsider the intersections between narrative construction, bodily experience, and the ethics of care. The analysis identifies two distinct yet interdependent modes of care within the memoir: form as care and care as form. The former refers to the ways in which the memoir’s structural choices (its polyphonic voice, generic hybridity, and experimental format) perform an ethics of care, both for the writer and the reader. The latter considers how representations of care (through acts, gestures, and their various manifestations) not only function as integral elements of the text’s overall design but also provide moments of respite and levity in an otherwise trauma-laden narrative. This paper foregrounds these dual modes and offers insights into the complexities of life writing in relation to the fractured autobiographical subject: a narrator caught between self-interrogation and self-preservation, a body that remembers trauma but lacks the physical evidence to validate its suffering. We argue that the arc of recovery, traced from trauma to care (personal and interpersonal), formalizes these tropes into an intertextual, self-diagnostic, non-linear, and playfully interactive structure of the memoir as life writing.